RANCANG BANGUN PROGRAM RUGI-RUGI LINTASAN GELOMBANG RADIO JARINGAN INDOOR BERBASIS GRAPHICAL USER INTERFACE (GUI) MATLAB - ., Budi (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
The loss was parameters influence in determining the site of its. This research designing programs path loss that can be used to a match model analysis .The program is based on Graphical User Interface designed in the platform of a GUIDE matlab .Platform consisted of the outdoor Cost231 Walfisch Ikegami and Models indoor Paulsen , Cost231 Multi Wall and One Slope , for analysis match model that Mean Error and Standard Deviation , the four this model will combined in forecasting losses the radio waves of an antenna transmitter outdoor up with the recipient in building , namely partner mart on Jl. Sultan Abdurahman Number 5-6 Pontianak City .The result of comparisons match the model used shows that the combination model Cost231 Walfisch Ikegami and Cost231 Multi Wall is model suitable than either combination other. The results of its value Mean Error the combination Model Cost231 Walfisch Ikegami-Cost231 Multi Wall 5,9 db to the system 3g and 10 db on system 4g , while combination Model Cost231 Walfisch Ikegami-Paulsen -20 db to the system 3g and -17,3 db on system 4g , combination Model Cost231 Walfisch Ikegami-One Slope 14,6 db to the system 3g and 12 db  on  system  4g  and  to  standard  deviation  smallest  is  a  combination  Model  Cost231  Walfisch Ikegami-One Slope with an 8 db regarding the Cost231 Walfisch Ikegami-Cost231 Multi Wall of the smallest 9,7 db and a combination of Model Cost231 Walfisch Ikegami-Paulsen with the standard 24,6 db it to the recommended no more than 10 db       Kata kunci : Path Loss, GUI, GUIDE, Model Propagasi.